2010
DOI: 10.1521/pedi.2010.24.6.746
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Dimensions of Normal and Pathological Personality and Childhood Maltreatment in Incarcerated Boys

Abstract: The relation between dimensions of normal and pathological personality and childhood maltreatment in incarcerated boys Nederlof, E.; van der Ham, J.M.; Dingemans, P.M.J.A.; Oei, T.I. Published in: Journal of Personality DisordersPublication date: 2010 Link to publication Citation for published version (APA):Nederlof, E., van der Ham, J. M., Dingemans, P. M. J. A., & Oei, T. I. (2010). The relation between dimensions of normal and pathological personality and childhood maltreatment in incarcerated boys. Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…One popular measurement tool used to assess the dimensional aspects of personality pathology at a trait level is the Dimensional Assessment of Personality Pathology Basic Questionnaire (see section on measures, DAPP-BQ; Livesley & Jackson, 2009) which has been validated in adolescent (Tromp & Koot, 2008, 2015, and in adult samples (Bagge & Trull, 2003;Livesley & Jackson, 2009). This converges with a recent increase in research focusing on the dimensions/traits of personality pathology in relation to abuse/neglect in children and adolescents (Gratz, Latzman, Tull, Reynolds, & Lejuez, 2011;Natsuaki, Cicchetti, & Rogosch, 2009;Nederlof, Van der Ham, Dingemans, & Oei, 2010) and young adults (Mathews, Kaur, & Stein, 2008). For example, a study on sexually victimized females by Wonderlich et al (2001) using the DAPP-BQ found that sexual abuse in childhood was associated with significantly elevated scores of the victimized group on lowerorder dimensions of the DAPP-BQ (e.g., Suspiciousness, Intimacy Problems, and Restricted Expression) when compared with a control group.…”
Section: Maltreatment and Personality Pathologymentioning
confidence: 57%
“…One popular measurement tool used to assess the dimensional aspects of personality pathology at a trait level is the Dimensional Assessment of Personality Pathology Basic Questionnaire (see section on measures, DAPP-BQ; Livesley & Jackson, 2009) which has been validated in adolescent (Tromp & Koot, 2008, 2015, and in adult samples (Bagge & Trull, 2003;Livesley & Jackson, 2009). This converges with a recent increase in research focusing on the dimensions/traits of personality pathology in relation to abuse/neglect in children and adolescents (Gratz, Latzman, Tull, Reynolds, & Lejuez, 2011;Natsuaki, Cicchetti, & Rogosch, 2009;Nederlof, Van der Ham, Dingemans, & Oei, 2010) and young adults (Mathews, Kaur, & Stein, 2008). For example, a study on sexually victimized females by Wonderlich et al (2001) using the DAPP-BQ found that sexual abuse in childhood was associated with significantly elevated scores of the victimized group on lowerorder dimensions of the DAPP-BQ (e.g., Suspiciousness, Intimacy Problems, and Restricted Expression) when compared with a control group.…”
Section: Maltreatment and Personality Pathologymentioning
confidence: 57%
“…One might speculate that the absence of the basic needs of food, clothing, shelter or medical attention characterized by neglect not only leads to other negative consequences (Gilbert et al, 2009), but also interferes with a person’s ability to enter into non-abusive intimate partner relationships. Speculating from one recent Dutch study that reported a link between emotional dysregulation and childhood abuse that depended on the co-occurrence of neglect (Nederlof, Van der Ham, Dingemans, & Oei, 2010), it is possible that childhood neglect may lead to greater emotion dysregulation which, in turn, renders a person more vulnerable to being victimized by IPV leading to injury. Drawing on the work of Dutton and colleagues (Dutton, 2003; Godbout, Dutton, Lussier, & Sabourin, 2009), it is also possible that childhood neglect disrupts the child’s attachments to parental figures and this leads to insecure adult attachment styles and, ultimately, marital violence in an attempt to control the partner and prevent threats of abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies into the association between specific types of maltreatment and personality are scarce, similar results have been previously documented. Nederlof and colleagues () found that emotional abuse is specifically related to neuroticism, whereas physical abuse is specifically associated with low agreeableness and dissocial behavior in a sample of incarcerated boys. Studies on psychological and personality disorders have also suggested similar specific relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maltreatment has been associated with emotional instability and neuroticism (Moran et al., ; Nederlof et al., ; Rogosch and Cicchetti, ), and also with enhancement and coping motives (Goldstein et al., ). These data suggest that maltreatment might be involved in several pathways to alcohol use, and not only deviance proneness.…”
Section: Positive Affect Regulationmentioning
confidence: 99%